Temperature rise of high-frequency martensite reorientation via Type II twin boundary motion in NiMnGa Ferromagnetic Shape Memory Alloy. (15th July 2015) - Pascan, O.-Z.; He, Y.J.; Moumni, Z.; Zhang, W.H.
Abstract : We measured the temperature rise of the high-frequency magnetic-field-induced martensite reorientation in Ni–Mn–Ga Ferromagnetic Shape Memory Alloy and observed the morphology of the associated twin boundaries. It was found that this temperature rise is mainly caused by low-friction Type II twin boundary motion, even though high-friction Type I twin boundary motion is dominant in quasi-static stress-induced martensite reorientation. A simple formula considering the frictional twin boundary motion and heat transfer is derived to describe this temperature rise.